1997
DOI: 10.1152/ajpendo.1997.273.4.e776
|View full text |Cite
|
Sign up to set email alerts
|

Age-related decreases in stimulatory G protein-coupled adenylate cyclase activity in osteoblastic cells

Abstract: In this study we examined parathyroid hormone (PTH)-, forskolin (FSK)-, and cholera toxin (CTX)-stimulated adenosine 3′,5′-cyclic monophosphate (cAMP) accumulation in rat osteoblastic cells (ROB) isolated from young (4 mo), mature (12 mo), and old (24–28 mo) male rats. Exposure to PTH increased cAMP accumulation in a concentration-dependent manner in all ROB cells examined. However, the maximum response in ROB from young rats was threefold greater than the maximum response in those from mature and old rats. Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…The cAMP cascade appeared to be already activated in senescent enterocytes, as revealed by their higher basal AC activity and cAMP levels. Increased basal cAMP content during aging and related diseases has also been observed in rat osteoblasts (Donahue et al, 1997) and brain tissue (Sugawa and May, 1993). It is possible that alterations in the expression of G proteins coupling the, as yet, putative intestinal cell PTH receptor to adenylyl cyclase may occur during senescence.…”
Section: Discussionmentioning
confidence: 98%
“…The cAMP cascade appeared to be already activated in senescent enterocytes, as revealed by their higher basal AC activity and cAMP levels. Increased basal cAMP content during aging and related diseases has also been observed in rat osteoblasts (Donahue et al, 1997) and brain tissue (Sugawa and May, 1993). It is possible that alterations in the expression of G proteins coupling the, as yet, putative intestinal cell PTH receptor to adenylyl cyclase may occur during senescence.…”
Section: Discussionmentioning
confidence: 98%
“…Among the GPCRs in Obs, the parathyroid hormone (PTH) receptor 1 has been extensively studied and recombinant PTH has been administered to treat age- and osteoporosis-related bone loss. However, aging also results in a defect in the stimulatory G protein coupling to adenylyl cyclase, which limits the bone’s response to PTH treatment (4). PTH receptor expression and the stimulatory effects of PTH on mesenchymal stem cells also decline with aging (5).…”
mentioning
confidence: 99%
“…Furthermore, aging impairs agonist-stimulated activity of second messengers such as cAMP and Ca 2+ (14,24), and Caf + signaling has been linked to the differentiation of cells from the mesenchymal lineage (4). We found that the percentage of cells displaying spontaneous [Ca 2+ h oscillations declined with age; significantly more ROB from young rats displayed spontaneous [Ca 2+ ]i oscillations than did ROB from old rats.…”
Section: Discussionmentioning
confidence: 99%
“…We cannot rule out the possibility that the cultures contain nonosteoblastic or preosteoblastic populations. However, the ROB display an osteoblastic morphology and express phenotypic markers of osteoblasts (i.e., alkaline phosphatase, type I collagen, osteopontin, and parathyroid hormone receptor) (14,24). It is possible that age-related differences in the degree of cellular heterogeneity of our cell populations contributed to differences in responsiveness to fluid flow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation